Lifetime measurement in 182W using the Differential Decay Curve Method - Zyriliou, Aikaterini; Mertzimekis, Theodoros; Vasileiou, Polytimos; Mavrommatis, Eirini; Chalil, Achment; Efstathiou, Margarita; Karadimas, Angelos; Bonatsos, Dennis; Martinou, Andriana; Minkov, Nikolay; Marginean, Nicolae; Mihai, Constantin; et al. (HNPS Advances in Nuclear Physics, 2024)
This work focuses on the lifetime measurement and spectroscopic properties of 182W. The mass region around this nucleus is of significant interest due to its unexplored nature and the presence of intriguing structural phenomena, including deformation, shape changes, and shape coexistence. Experimental measurements were conducted in the National Laboratory IFIN-HH in Romania, focused on the spectroscopic study of 182W isotope using the Differential Decay Curve Method (DDCM), a similar approach for the Recoil Distance Doppler Shift (RDDS) method. This experiment provided valuable data on the energy levels, lifetimes, and decay properties of the excited states in the 182W and neighboring nuclei. The measurements were performed using the ROSPHERE detector array, loaded with HPGe and particle identification detectors, and a plunger device. As a result, the lifetime for the 61+ in 182W obtained for the first time via the fusion evaporation reaction 181Ta(11B, 10Be)182W and the DDCM at 47 MeV, and was found to agree well with earlier measurements.